(untitled) (Research, Society and Development, 2022)
Childhood and adolescent cancer can affect individuals under 20 years of age, being a rare diagnosis, but with great biopsychosocial repercussions in patients and their families. Advances in information health information technology (HIT) have provided the increasing use of electronic registration systems as a tool in coping with various diseases. The aim of this study was to develop and implement a clinical database (DB) of children and adolescents with cancer. The characteristics and applicability of this DB were defined from the needs of the hospital involved in the research and guided by the review of the specialized literature. For the construction of DB, the web platform for electronic capture of research data (REDCap), accessible through the partnership with the REDCap consortium. The data entered in the DB were from patients under 20 years of age, diagnosed with cancer, undergoing chemotherapy. We analyzed 60 medical records that met the eligibility criteria. There were 103 hospitalizations for febrile neutropenia, and 89.3% (92) did not evolve with severity, while 10.7% (11) required treatment in an intensive care unit. Socioeconomic and demographic data on cancer diagnosis, disease stage and treatment were also collected. Even in environments with limited resources, it is possible to have access to quality information for facing childhood cancer through IT solutions such as the REDCap platform. Future studies may be conducted with the cooperation of various institutions that treat children and adolescents with cancer, providing a robust evidence base for clinical and translational research.